(untitled) (The Research of Medical Science Review, 2025)
Objective: This study aimed to evaluate the correlation and agreement between splenic volume measurements obtained using ultrasonography (US) and computed tomography (CT), in order to assess the reliability of US as an alternative to CT for spleen volumetry in adults without known splenic pathology. Methodology: All 100 patients underwent contrast-enhanced abdominal CT followed by an ultrasound within 72 hours. Splenic volume on CT was calculated using semi-automated segmentation with 3D reconstruction, while US volumes were derived using the prolate ellipsoid formula (0.523 × Length × Width × Thickness). Pearson’s correlation, linear regression, Bland–Altman analysis, and intraclass correlation coefficients (ICC) were used to assess the correlation and agreement between modalities. Results: The mean splenic volume measured by CT was 231.5 ± 52.4 mL, while ultrasound measured 219.8 ± 49.3 mL. A strong positive correlation was observed (r = 0.87, p < 0.001), with a regression equation of CT = 1.12(US) + 4.7 and R² = 0.76. Bland–Altman analysis showed a mean difference of 11.7 mL, with most values within ±50.8 mL. ICCs for CT and US were 0.96 and 0.91, respectively, indicating excellent inter-observer reliability. Subgroup analysis revealed slightly better accuracy in individuals with BMI ≤25. Conclusion: Ultrasound demonstrates strong correlation and acceptable agreement with CT in spleen volumetry, making it a reliable, non-invasive, and accessible alternative when CT is not feasible